Menelusur Sejarah, Mengurai Sastra: Fungsi Mitos Ajaran Dewa dalam Babad Kayu Salem terhadap Kehidupan Manusia - Hilyati, Aalaa (Crises on Languages and Literature, 2025)
Myths are falling out of favor in modern society, as they are seen as irrelevant. To address the current perspective, this study aims to describe and interpret various myths about the Gods' teachings to humans. Babad Kayu Selem is a historical text that traces the origins of the Pasek Kayu Selem family to the sudra or vaishya class. The material object used in this study is Babad Kayu Selem, which was translated by I Wayan Wardha in 1989. Three methods are used in this study. The first method is data collection through a literature review. The second method was data analysis, which was carried out in two stages in this study. First, describing various myths of teachings in Babad Kayu Selem. Second, the data, in the form of collected myths and teachings, are interpreted using a historical approach, drawing on historical literature as interpreted by Kuntowijoyo, and linked to the function of myths based on the Human, Myth, and Mythology approach as interpreted by Zeffry. The third method is to present the analysis results descriptively. The results of the study, through reading the Babad in comprehension and creation modes, show that the myths in Babad Kayu Selem fulfill their functions, as reflected in social facts, so they can be said to be part of history and culture that influence aspects of human life. In the end, Babad Kayu Selem highlights their enduring influence on cultural identity and social values, inspiring current society to understand that these narratives can strengthen community ties and foster a sense of belonging.